Effect of Shade and Mulch on Germination of Adina cordifolia Hook - Beniwal, B. S.; Joshi, S. R.; Dhawan, V. K. (Indian Forester, 1990)
Tbe paper presents the results of an experiment conducted at Forest Research Institute, Dehra Dun to see the effect of shade and mulch on the germination of Adina cordifolia. The results after analysis of the data indicate that use of mulch gives quick and higher germination of seed.